Port of Pulupandan tide model. - Gregorio, Enrico G. (Philippine Engineering Journal)
This paper describes the physical model study of the Port of Pulupandan siltation problem. A fixed distorted model (1: 250 horizontal, 1:50 vertical) reproduces the prototype hydrography. The model uses the Froude criteria but simulation is limited to the tidal variation only. The study is focused on identification and reduction of eddy zones. Four basic layouts and its modifications are tested. The results of the model investigation lead into the selection of Alternative No. 3 layout that produces promising flow pattern and smaller eddy zones. The selected layout not only exhibits streamlined flow but also entails minimum disturbance to the existing facilities hence less capital investment is involved.